Sweet Potatoes - Marr, Charles W.; Tisserat, Ned (My University, 1998)
This publication is for commercial vegetable production, specifically the production of sweet potatoes in Kansas.
MF1110_1998_11
Keywords: MF1110; Crops; Fruits and Vegetables; Equipment and Structures; MF